Big Mitogen-Activated Protein Kinase 1 Protects Cultured Rat Aortic Smooth Muscle Cells From Oxidative Damage - Jing Zhao; Yoji Kyotani; Satoyasu Itoh; Hitoshi Nakayama; Minoru Isosaki; Masanori Yoshizumi (Elsevier, 2011)
Abstract.: Oxidative stress is considered a major mediator of arteriosclerosis. In vascular smooth muscle cells, oxidative stress-induced cell death (including apoptosis) is probably related to arterial calcification in arteriosclerosis. Big mitogen-activated protein kinase-1 / extracellular signal-regulated kinase 5 (BMK1/ERK5) is a newly identified member of the mitogen-activated protein kinases family. Like Src tyrosine kinase, BMK1/ERK5 is known to be sensitive to oxidative stress; however, its pathophysiological significance is poorly understood. In this study, we investigated the involvement of BMK1 and Src in H2O2-induced cell death using cultured rat aortic smooth muscle cells (RASMCs). Cell apoptosis was evaluated by using the TdT-mediated dUTP nick end labeling (TUNEL) method, and BMK1 and Src activities were determined by Western blotting. The main results are as follows: 1) BMK1 and Src were activated by H2O2 in a time- and concentration-dependent manner in RASMCs; 2) BMK1 activation by H2O2 was attenuated both in Src-knockdown RASMCs and in RASMCs pretreated with 4-amino-5-(4-chloro-phenyl)-7-(t-butyl) pyrazolo[3,4-d]pyrimidine (PP2), a Src family kinases inhibitor; and 3) H2O2-induced cell death was increased in BMK1- and Src-knockdown RASMCs as well as in PP2-treated RASMCs. These findings suggested that Src and BMK1 may play defensive and resistive roles against oxidative stress-induced death in RASMCs. Keywords:: arteriosclerosis, smooth muscle cell, big mitogen-activated protein kinase-1 (BMK1), calcification, oxidative stress